The Impact of Geometrical Spinal Shape on Fresh Vertebral Fractures in Elderly Volunteers: A Longitudinal Cohort Analysis. Issue 19 (1st October 2020) - Yamada, Tomohiro; Yamato, Yu; Sato, Yoshihiro; Togawa, Daisuke; Hasegawa, Tomohiko; Yoshida, Go; Yasuda, Tatsuya; Arima, Hideyuki; Banno, Tomohiro; Oe, Shin; Ushirozako, Hiroki; Ide, Koichiro; et al.
Abstract : Study Design: Four-year, longitudinal cohort study. Objective: The aim of this study was to investigate the effect of original spinal shape on incidental vertebral fractures (VFs) and to identify the influence of changes in pre- and post-fracture geometrical spinal shape. Summary of Background Data: Clinical evidence demonstrates that VFs cause spinal kyphosis, morbidities, and deteriorating quality of life in elderly people. However, knowledge of geometrical spinal shapes that affect incidental VFs is limited. Methods: Three hundred seventeen volunteers underwent whole spine radiography as part of a health screening in both 2012 and 2016. We extracted volunteers with incidental VF in 2016. Sex- and age-matched volunteers without VF were enrolled as controls. Baseline demographic variables, geometrical spinal shape, and spinopelvic parameters were compared between the two groups. In volunteers with incidental VF, we investigated the association between baseline spinal shape and post-fracture shape. Results: Twenty-seven volunteers (12 men; mean age 75.4 ± 5.4 and 15 women; mean age 71.6 ± 7.9) with VF were enrolled, and 175 volunteers (48 men, 127 women) without VF were selected as controls. In men with VF, the thoracic kyphosis apex was located significantly more posteriorly and caudally than in those without VF. In women with VF, the lordosis apex was located significantly more posteriorly and caudally than in those without VF. After fractures occurring above the inflexion vertebra, the low anterior apex spine (L5) changed its geometrical shape in that the posterior apex and the inflexion vertebra shifted significantly more posteriorly compared to the high anterior apex spine (L4/5). Conclusion: Original geometrical spinal shape affected the occurrence of VF, and post-fracture spinal shape depended on the positional relationship between the inflexion vertebra and fractured vertebra. Our study helps to understand the influence of geometrical spinal shape on the risks of VF. Level of Evidence: 3 Abstract : This study is the first study to evaluate the effect of geometrical spinal shape on vertebral fractures. Our results suggest that an original spinal shape with apices and inflexion located more posteriorly and caudally is a potential new risk factor for new vertebral fracture.